2015
DOI: 10.12659/msm.892246
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control Rate of T2DM Outpatients in China: A Multi-Center Survey

Abstract: BackgroundType 2 diabetes mellitus (T2DM)-associated mortality and morbidity are strongly dependent on glycemic control. With T2DM prevalence increasing in China, we aimed to assess glycemic control rates in Chinese T2DM outpatients.Material/MethodsA total of 9065 adult T2DM outpatients (5035 men) were assessed in 26 Chinese medical centers between August 2010 and April 2012. Patients were stratified according to BMI (kg/m2): <24, 24–28, and >28. Successful glycemic control was defined as glycated hemoglobin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 24 publications
2
19
3
Order By: Relevance
“…However, at present, glycemic control is less than ideal all over the world. A cross-sectional study of 9065 T2DM outpatients from 26 medical centers in China found that blood glucose levels were controlled in only 32.6% of patients [ 27 ],which was similar to the rate of 31.78% among 238,639 diabetes patients reported by Ji et al in 2013 [ 28 ]. The International Diabetes Mellitus Practice Study [ 29 ] included 11,799 patients from 17 countries in Eastern Europe, Africa, South America, and Latin America and found a blood glucose-control rate of only 25%.…”
Section: Discussionsupporting
confidence: 62%
“…However, at present, glycemic control is less than ideal all over the world. A cross-sectional study of 9065 T2DM outpatients from 26 medical centers in China found that blood glucose levels were controlled in only 32.6% of patients [ 27 ],which was similar to the rate of 31.78% among 238,639 diabetes patients reported by Ji et al in 2013 [ 28 ]. The International Diabetes Mellitus Practice Study [ 29 ] included 11,799 patients from 17 countries in Eastern Europe, Africa, South America, and Latin America and found a blood glucose-control rate of only 25%.…”
Section: Discussionsupporting
confidence: 62%
“…[ 23 , 25 , 26 ]. In another study that used age rather than duration of diabetes, greater age was an independent risk factor for poor glycemic control, which is consistent with our study [ 27 ]. Therefore, the age differences in our study may have arisen from the longer duration of diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Diabetes mellitus, a chronic and systematic metabolic condition, has become a global health problem. The hyperglycemic condition is an important etiologic factor leading to numerous debilitating complications that also influence various cellular and organ functions [ 31 , 32 ]. In 1935, urological complications of diabetes were recognized, including DCP, which have a profound effect on the quality of life of diabetic patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%